Potential effect of probiotics in the treatment of breast cancer - Luis Mendoza (Frontiers Media S.A., 2019)
Breast cancer is one of the most important causes of cancerrelated morbidity and mortality in the world. Probiotics, as functional food, have the potential to act against breast cancer, as evidenced by cell-based and animal model experiments. Probiotic may be useful in prevention or treatment of breast cancer by modulating the gastrointestinal bacteria and the systemic immune system. However, large-scale clinical trials and intensive research are mandatory to confirm the in vitro and in vivo results and exploring the probiotics-related metabolic, immune, and molecular mechanisms in breast cancer. This current review summarizes the available data related to probiotics and their potential role in the treatment of breast cancer.